CTIM-28. MULTILAMELLAR MRNA LIPID PARTICLES INDUCE IMMUNOLOGIC REPROGRAMMING IN CANINE AND HUMAN GLIOBLASTOMA PATIENTS. (14th November 2022) - Mendez-Gomez, Hector; DeVries, Anna; Stover, Brian; Zhang, Dingpeng; Grippin, Adam; Von Roemeling, Christina; Weidert, Frances; Karachi, Aida; Qdaisat, Sadeem; Thomas, Nagheme; McGuiness, James; Castillo, Paul; et al.
Abstract: BACKGROUND: Although mRNA vaccines have been deployed with great success against COVID-19, unlocking this technology against glioblastoma will necessitate new lipid-nanoparticle formulations that overcome cancer tolerance and immunosuppression. OBJECTIVE/METHODS: We sought to develop a novel mRNA vaccine system to make tolerogenic tumor antigens appear more dangerous through use of unmodified nucleosides (pathogen associated molecular patterns, PAMPs) and highly cationic lipid shells that elicit a systemic damage response against cancer antigens. RESULTS: We developed a novel vaccine formulation that increases payload packaging of tumor amplified mRNA into multilamellar (onion-shaped) particles for systemic (intravenous) administration. We demonstrate significant immunogenicity and efficacy of multilamellar RNA-NPs in syngeneic murine models for high-grade glioma (KR158b-pp65), and diffuse midline glioma (H3K27M DMG). Remarkably, RNA-NPs significantly improve median survival outcomes of DMG bearing mice beginning therapy at endpoint (Day 35 after midline intracranial implantation). Unlike prototypical mRNA vaccines that activate endosomal toll-like receptors (i.e. TLR7), multilamellar RNA-NPs elicit immunologic response predominantly through intracellular pathogen recognition receptors (RIG-I); long-term survival benefits from RNA-NPs were completely abrogated in RIG-I knockout mice. In canines (pet dogs) with spontaneous gliomas, RNA-NPs elicit massive recruitment/activation of peripheral blood mononuclear cells (PBMCs) which correlate with their trafficking into lymphoreticular organs (in follow-up murine studies). In canines receiving neoadjuvant RNA-NPs, prior to glioma biopsy, we see significant reprogramming of the glioma microenvironment with increased gene signatures for antigen processing/presentation, interferon signaling and cytotoxicity. Upon translation into human clinical trials for glioblastoma patients (NCT04573140), RNA-NPs elicit rapid (within hours) release of cytokines (e.g. IL-1, IL-6, IL-12 TNF-α, interferons) and chemokines (e.g. MIP1α, MCP-1, IP-10), which correlate with mobilization of PBMCs and activation of dendritic cells/CD8 lymphocytes. CONCLUSION: First-in-human application of systemic multilamellar RNA-NP vaccines results in significant biologic effects and rapid immunologic reprogramming.